Drivers of ecological environment changes in the Baozhainao lake-basin system, Ordos Basin - Yanying Lu; Wenke Wang; Ming Zhao; Zhitong Ma; Zicheng Yan; Jiangnana Jing (地质科技通报, 2023)
In arid and semiarid regions, lake-basin ecosystems are an important part of watershed security barriers, playing an important role in maintaining the stability of ecological patterns. However, the ecological environment of the lake-basin system has been gradually degraded in recent years, and its change process is accompanied by a complex dynamic mechanism. In the present study, we explored the spatial variability of the ecological environment of the lake-basin system and its drivers by taking Baozhainao Lake in the Mu Us Sandy Land of the Ordos Basin as the study area.In-situ dynamic monitoring, sample survey, statistical analysis and numerical simulation were employed. The distribution patterns of typical vegetation in the basin were determined and the mechanisms underlying the mutual feedbacks between subsurface hydrological process and lakeshore ecosystem was explored. The results show that the Baozhainao lake-basin ecosystem consists of four zoning types, namely, the lake zone, the lake nearshore fluctuation zone, the lakeshore beach zone, and the lakeshore wind beach zone. From the lake to the beach zone, the depth of water table increased gradually and the vegetation type transitions from water-loving and salt-tolerant to drought-tolerant. It was further found that the presence of vegetation on the lake shore significantly affects the circulation mode of the groundwater flow system. The conversion between lake and groundwater occurs mainly in the local groundwater flow system, resulting in a significant reduction in groundwater recharge to the lake.The results of this study can provide a scientific basis for the restoration and conservation of plant species diversity and vegetated ecosystems in the lake nearshore fluctuation zoneand lakeshore wind beach zone in arid regions.